A micro-machined flow sensor formed on copper on a polyimide substrate and its application to respiration measurement. (21st May 2019) - Kato, Ayami; Hasegawa, Yoshihiro; Taniguchi, Kazuhiro; Matsushima, Miyoko; Kawabe, Tsutomu; Shikida, Mitsuhiro
Abstract: We developed a respiration sensor integrated with a temperature compensation sensor to a flow sensor on copper on a polyimide substrate, and applied it to respiration measurement at different temperatures of exhalation and inhalation. We demonstrate that the change in the respiration sensor outputs is almost constant, regardless of the change in fluid temperature. Then, we conducted animal experiments using a rat and a rabbit, and verified the respiration measurement function of the sensor. Thanks to the temperature compensation function, we could measure the respiration of both the rat and rabbit despite the difference in temperature between exhalation and inhalation. In addition, the sensor could measure the change in respiration cycle due to the depth of anesthesia. We confirm that the fabricated sensor can be applied to respiration measurement in which temperature changes between exhalation and inhalation.